2012
DOI: 10.1002/ijc.27489
|View full text |Cite
|
Sign up to set email alerts
|

Protein pathway activation mapping reveals molecular networks associated with antiestrogen resistance in breast cancer cell lines

Abstract: Previously, we have identified a panel of breast cancer antiestrogen resistance (BCAR) genes. Several of these genes have clinical relevance because mRNA or protein levels associate with tamoxifen resistance or tumor aggressiveness. We postulated that changes in activation status of protein signaling networks induced by BCAR genes may provide better insight into the mechanisms underlying antiestrogen resistance. Key signal transduction pathways were analyzed for changes in activation or expression using revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
2
27
0
1
Order By: Relevance
“…94 On the other hand, gene transcription analyses and pathway activation mapping have revealed that overexpression of BCAR3 or BCAR1 activates signaling networks that have not only common elements but also distinctive features. 109,120 Taken together, these findings highlight the complexities in the activities of NSP and CAS proteins and their modules, which remain to be further unraveled in future studies.…”
Section: Monographsmentioning
confidence: 78%
See 1 more Smart Citation
“…94 On the other hand, gene transcription analyses and pathway activation mapping have revealed that overexpression of BCAR3 or BCAR1 activates signaling networks that have not only common elements but also distinctive features. 109,120 Taken together, these findings highlight the complexities in the activities of NSP and CAS proteins and their modules, which remain to be further unraveled in future studies.…”
Section: Monographsmentioning
confidence: 78%
“…101,102 AKT activation downstream of PI3 kinase may also contribute to BCAR3-dependent antiestrogen resistance. 102,109 Another key role of BCAR3 likely contributing to estrogen-independent growth involves increasing the activity of SRC recruited to BCAR1, thus leading to not only phosphorylation of the BCAR1 substrate domain and subsequent CRK-RAC1 signaling 21,37,89,99,101,102 but likely also other SRC-dependent activities. 108,[110][111][112] Interestingly, endogenous BCAR3 has also been found to mediate some of the proliferative effects of the EGF receptor in the nontransformed MCF12A human breast cell line, suggesting that a similar cross-talk with the EGF receptor might also play a role in breast cancer cell proliferation and antiestrogen resistance.…”
mentioning
confidence: 99%
“…These IC 50 values were similar to those needed to induce internalization and degradation of HER3 receptors. Given upregulation of HER3 has been found to be a major mechanism underlying drug resistance to EGFR and HER2 tyrosine kinase inhibitors (for example lapatinib, gefitinib, erlotinib) [12-14], we next assessed the effect of perhexiline combined with lapatinib, an agent commonly used to treat HER2-positive breast cancer. Treatment of MDA-MB-468 cells with 100 nM lapatinib for 2 hours led to decreased phosphorylation and activation of HER3 and downstream Akt signaling (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, clinical efficacy is not satisfactory as drug resistance reduces durable responses. Upregulation of HER3 has been found as one of the major mechanisms underlying drug resistance to EGFR and HER2 tyrosine kinase inhibitors (for example lapatinib, gefitinib, erlotinib) and to endocrine therapy in the treatment of breast cancer [12-14]. For example, it has been shown that the expression of HER3 ligand heregulin (HRG) as well as activation of HER3 signaling is involved in resistance to anti-estrogen therapies in vitro and in vivo [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…Protein microarrays have been used extensively for characterizing signaling pathways in various cancers including prostate cancer [83], ovarian cancer [84], and T-cell acute lymphoblastic leukemia [85]. In addition, protein microarray technology has also been used to identify molecular networks associated with antiestrogen resistance in breast cancers [86], to monitor response to kinase inhibitors [87], and to study aberrant activation of signaling molecules in head and neck cancers [88]. Peptide microarrays are also being used for high-throughput screening of kinase substrates and also to characterize motifs recognized by specific kinases [33,89].…”
Section: Protein and Peptide Microarray Strategies To Study Signalingmentioning
confidence: 99%